Effect of different curing times and distances on the microhardness of nanofilled resin-based composite restoration polymerized with high-intensity LED light curing units - Haifa Barakah (Elsevier, 2021)
Purpose: This study examined the effect of different distances and curing times on the microhardness (VHN) of nanofilled resin-based composite (RBC) restorations polymerized with high-intensity LED LCUs. Materials and methods: Seventy-five RBC specimens (2 mm thickness and 5 mm diameter) were fabricated from Tetric-N-Ceram (Ivoclar Vivadent). Each of the 25 specimens was polymerized by means of one of three types of high-intensity LED LCUs: (B) Blue-Phase-G2 (polywave LED, Ivoclar Vivadent), (E) Elipar S10 TM (single-peak, 3 M ESPE), and (P) Planmica Lumion (single-peak, Mectron) at three different distances (0 mm, 2 mm, and 4 mm) at 20 sec, 40 s, and 60 sec. A microhardness tester (NOVA, Innovatest, The Netherlands) was used to measure the VHN from the top and bottom surfaces. Data for VHN were analyzed using mixed ANOVA, followed by post hoc analyses with p-values < 0.05. Results: A significant difference was found in VHN between all three LED LCUs, where (B) specimens had the highest means, followed by (E) and (P). Bottom surface VHN values were reduced significantly (p < 0.05) compared to top surface values in all LCU types. With increasing distances up to 2 mm and 4 mm, VHN values with (E) and (P) were significantly reduced on the top and bottom surfaces (p < 0.05). When the curing times were increased for 40 and 60 sec, the VHN values were significantly improved (p < 0.05). Meanwhile, increasing the distance with (B) did not significantly reduce the VHN. Moreover, increasing the curing times did not significantly improve the VHN of the bottom surfaces. Conclusion: High-intensity LCUs have variable effects on the surface (top/bottom) hardness of Tetric-N-Ceram nanofilled RBC restoration. With increasing distance, VHN was reduced; therefore, compensation with more curing time (2 mm/40 sec and 4 mm/60 sec) is highly recommended with Elipar S10 and Planmica Lumion LCUs to improve the material surface hardness.